Star Wars VII e il simulacro dello spettacolo - Rabbito, Andrea (Scenari, 2021)
Star Wars VII: The Force Awakens represents the intent of current American cinematography to recover the spirit of cinema in the ’80s; the film by Abrams realize a semblance-film of the blockbuster of the ’80s that characterizes contemporary cinema and proposes a dynamic described by Borges with the story of Pierre Menard.